Effects of mercury on human polymorphonuclear leukocyte function in vitro. - Contrino, J. (1988)
A variety of heavy metals are recognized as environmental pollutants, and although a significant body of literature exists on the acute toxicity of these metals in various tissues, little is known about the effects of metals such as mercury on host defense. Therefore, the effect of mercuric chloride (HgCl2) on human polymorphonuclear leukocytes (PMN) function in vitro was evaluated. The acute toxicity of HgCl2 for human PMN was calculated initially using vital dye exclusion (trypan blue), and lactate dehydrogenase (LDH) release. Concentrations of HgCl2 less than or equal to 10(-6) M did not induce significant LDH release, or uptake of trypan blue. Additionally, HgCl2 at less than or equal to 10(-7) M produced no ultrastructural alterations in the PMN. The effects of HgCl2 on human PMN functions involved in host defense were evaluated next. HgCl2 consistently suppressed human PMN adherence, polarization, chemotaxis, and erythrophagocytosis at concentrations between 10(-6) and 10(-17) M. Because of the established role of oxygen metabolites in host defense, the effects of HgCl2 on human PMN chemiluminescence and H2O2 production were evaluated next. These studies demonstrated that low concentrations of HgCl2 (ie, 10(-9)-10(-15) M) significantly enhanced chemiluminescence, as well as stimulated H2O2 production by the PMN. These studies clearly demonstrate the ability of extremely low levels of HgCl2 not only to suppress various PMN functions involved in host defense, but also to stimulate oxygen metabolism. In vivo, these HgCl2 effects would not only compromise host defense but also promote tissue injury via the local production of oxygen metabolites.